ANALYSIS OF THE THINKING PROCESS OF GRADE XI STUDENTS IN SOLVING MATHEMATICS PROBLEMS REVIEWED FROM THE EXTROVERT AND INTROVERTED PERSONALITIES OF STUDENTS OF SMK PGRI 24 JAKARTA - Amri, Saeful (PT. Antis International Publisher, 2025)
Objective: I conducted research with the aim of training and determining the skills of students at SMK PGRI 24 Jakarta. Students' ability to think and solve math problems is examined from the perspective of introverted and extroverted students. Method: To make my research easier, I used a qualitative approach. Six Class XI students from SMK PGRI 24 in Jakarta were the subjects of the study; The three participants each represented extroverted and introverted personality types. Questionnaire, interview, and documentation approaches were used to collect data for this study. To collect this data, aspects of the student's personality were considered, along with testing the data and the conclusions drawn from the participants. A triangulation approach was used to collect data for the study. Results: The study found that introverted and extroverted students were at a full level of understanding of the difficulties used in their thought processes as well as carrying out planning, evaluation, and monitoring procedures. Planning steps are followed, which are completed by having students double-check the planning procedures. According to the results of the research interviews, extroverted students were at the level of tacit use, and introverted students were at the level of strategic use. Novelty: Students' ability to think and solve math problems is examined from the perspective of introverted and extroverted students.